Force and time-dependent self-assembly, disruption and recovery of supramolecular peptide amphiphile nanofibers. (10th May 2018) - Dikecoglu, F Begum; Topal, Ahmet E; Ozkan, Alper D; Tekin, E Deniz; Tekinay, Ayse B; Guler, Mustafa O; Dana, Aykutlu
Abstract: Biological feedback mechanisms exert precise control over the initiation and termination of molecular self-assembly in response to environmental stimuli, while minimizing the formation and propagation of defects through self-repair processes. Peptide amphiphile (PA) molecules can self-assemble at physiological conditions to form supramolecular nanostructures that structurally and functionally resemble the nanofibrous proteins of the extracellular matrix, and their ability to reconfigure themselves in response to external stimuli is crucial for the design of intelligent biomaterials systems. Here, we investigated real-time self-assembly, deformation, and recovery of PA nanofibers in aqueous solution by using a force-stabilizing double-pass scanning atomic force microscopy imaging method to disrupt the self-assembled peptide nanofibers in a force-dependent manner. We demonstrate that nanofiber damage occurs at tip-sample interaction forces exceeding 1 nN, and the damaged fibers subsequently recover when the tip pressure is reduced. Nanofiber ends occasionally fail to reconnect following breakage and continue to grow as two individual nanofibers. Energy minimization calculations of nanofibers with increasing cross-sectional ellipticity (corresponding to varying levels of tip-induced fiber deformation) support our observations, with high-ellipticity nanofibers exhibiting lower stability compared to their non-deformed counterparts. Consequently, tip-mediated mechanical forces can provide an effective means of altering nanofiber integrity and visualizing the self-recovery of PA assemblies.